2023
DOI: 10.3390/foods12051073
|View full text |Cite
|
Sign up to set email alerts
|

Blackcurrant Alleviates Dextran Sulfate Sodium (DSS)-Induced Colitis in Mice

Abstract: Previous studies have reported that anthocyanin (ACN)-rich materials have beneficial effects on ulcerative colitis (UC). Blackcurrant (BC) has been known as one of the foods rich in ACN, while studies demonstrating its effect on UC are rare. This study attempted to investigate the protective effects of whole BC in mice with colitis using dextran sulfate sodium (DSS). Mice were orally given whole BC powder at a dose of 150 mg daily for four weeks, and colitis was induced by drinking 3% DSS for six days. Whole B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…It is widely believed that anti-inflammatory cytokines play a crucial role in regulating the function between the intestinal barrier and intestinal epithelium, whereby increased intestinal permeability allows for a malfunctioning of the immune response to intestinal bacterial antigens, which in turn triggers intestinal inflammation [46,52] . Damage to intestinal epithelial cells caused by CS was reported to worsen the inflammatory response by increasing the generation of pro-inflammatory cytokines [15] , such as TNF-α, IL-1β and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that anti-inflammatory cytokines play a crucial role in regulating the function between the intestinal barrier and intestinal epithelium, whereby increased intestinal permeability allows for a malfunctioning of the immune response to intestinal bacterial antigens, which in turn triggers intestinal inflammation [46,52] . Damage to intestinal epithelial cells caused by CS was reported to worsen the inflammatory response by increasing the generation of pro-inflammatory cytokines [15] , such as TNF-α, IL-1β and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal immune responses in the gut are a feature of colitis [35], which is characterized by the increase of inflammatory cytokines (TNF-α, IL-1β, IL-6, etc) and decrease of anti-inflammatory cytokines, such as IL-10, and these changes are observed in patients with IBD [36] and DSS-induced colitis mice [37]. The results of the current study revealed the changes in cytokine levels resulting from immunological abnormalities caused by DSS in the gut were attenuated by L. plantarum, COS, and the synbiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Antosianin merupakan golongan flavonoid yang banyak terdapat pada buah dan sayuran berwarna gelap, antara lain kubis ungu, anggur ungu, blueberry, ceri, raspberry, beras hitam (D. Li et al 2015), banyak terkandung pada ubi jalar ungu (Rahmah, Ramdan, and Lestari 2023). Tanaman blackcurrant kaya akan kandungan antosianin (Moon, Cha, and Kim 2023). Antosianin merupakan pigmen berwarna yang larut dalam air yang termasuk dalam kelompok fenolik.…”
Section: Pendahuluanunclassified